Evolución de los pacientes pediátricos con diagnóstico de hidronefrosis que consultaron al Hospital Universitario San Vicente Fundación, Medellín, Colombia, entre 1960 y 2010 (2014)
ABSTRACT: Hydronephrosis is one of the most common congenital malformations detected on prenatal ultrasounds. Moderate and severe cases are often associated with urological abnormalities. Objective: To describe the causes of hydronephrosis, and the frequency of its prenatal diagnosis and of chronic kidney disease (CKD) in a series of pediatric patients. Materials and methods: A descriptive, retrospective study of 924 patients under 18 years of age seen at a university hospital in Medellín, Colombia, between 1960 and 2010. Results: 64.3% were male. Diagnosis was prenatal in 133 (14.4%). Hydronephrosis was bilateral in 198 patients (28.5%). In 169 (18.3%) no associated urological abnormality was found; 7 of these (4.2%) reached CKD. Ureteropelvic stenosis was diagnosed in 216 (23.3%) followed by vesicoureteral reflux in 199 (21.5%) and posterior urethral valves in 87 (9.4%); 93 (10.2%) reached CKD. When hydronephrosis was diagnosed by urography, patients developed CKD in 11.3% vs. 8.4% in those whose diagnosis was made by ultrasound; frequency of CKD was 4.8% when diagnosis by ultrasound was prenatal, and 10.8% when it was postnatal. Conclusion: Early diagnosis of hydronephrosis allows the detection of urologic abnormalities susceptible to treatment. There is controversy about the best imaginological method for the follow-up of these patients.